2022
DOI: 10.1186/s43591-022-00027-1
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene terephthalate nanoparticles effect on RAW 264.7 macrophage cells

Abstract: Plastic pollution is a major environmental concern due to its pervasiveness which continues to increase year on year, as a result of a continuing acceleration in global plastic production and use. Polyethylene terephthalate (PET) is among the most produced plastics, commonly used as food and beverage containers. Once released in the environment, the degradation of plastic materials produces micro-and nano-plastics, with a particular concern about potential toxicological effects if they cross epithelial barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 58 publications
(65 reference statements)
1
16
0
Order By: Relevance
“…When cells were exposed to 100 µg mL −1 of PE Au or PVC Au nanoplastics, both the RAW 264.7 and Caco-2 cells showed cell interaction and internalization, detected by each technique that was applied. In particular, nanoplastics were mainly distributed inside endosomes, with amphisomes, confirming the endo-phagocytic pathway of plastics [ 23 ] and outside interactions with the cell membrane and microvilli.…”
Section: Discussionmentioning
confidence: 87%
“…When cells were exposed to 100 µg mL −1 of PE Au or PVC Au nanoplastics, both the RAW 264.7 and Caco-2 cells showed cell interaction and internalization, detected by each technique that was applied. In particular, nanoplastics were mainly distributed inside endosomes, with amphisomes, confirming the endo-phagocytic pathway of plastics [ 23 ] and outside interactions with the cell membrane and microvilli.…”
Section: Discussionmentioning
confidence: 87%
“…However, using dental pulp stem cells, Ma et al showed that nylon-11 nanoparticles (approximately 50 nm) were cytocompatible at a dose of 400 µg/mL [ 51 ]. Nanoparticles comprising another commodity plastic, PET, were recently tested in multiple studies with RAW 264.7 cells [ 36 , 37 , 81 ]. At concentrations of 15 µg/mL, Aguilar-Guzmán and colleagues showed the PET nanoparticles affected RAW 264.7 cells by increasing the production of ROS, altering cell proliferation, and upregulating certain genes likely related to foreign particle responses and cell maintenance [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nanoparticles comprising another commodity plastic, PET, were recently tested in multiple studies with RAW 264.7 cells [ 36 , 37 , 81 ]. At concentrations of 15 µg/mL, Aguilar-Guzmán and colleagues showed the PET nanoparticles affected RAW 264.7 cells by increasing the production of ROS, altering cell proliferation, and upregulating certain genes likely related to foreign particle responses and cell maintenance [ 81 ]. For nylon-based NPs, future studies are required to understand the potential effects of these particles on gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…The size of the nanoparticles also influences composition of the protein corona; small plastic particles have been known to favor the formation of soft corona, while large plastic particles favor the formation of hard corona ( Kihara et al, 2019 ). Relatively small micro- or nanoplastics may be uptaken either through phagocytosis or receptor-mediated processes, particularly by phagocytes such as macrophages ( Aguilar-Guzmán et al, 2022 ). Further research is necessary to investigate the changes to the corona composition, and the potential role of its uptake into specific cells.…”
Section: Discussionmentioning
confidence: 99%